DIP applications handbook: document image processing - Perkin, Simon (Comp.) (NCC Blackwell OxfordGB, 1991)
Provides a comprehensive picture of the state of the market. Deals with aspects of DIP technology and presents vendor and NCC case studies. Attempts to make potential DIP users aware of suppliers and their products.